Kajian Kenaikan Harga BBM 1 Maret 2005 Terhadap PDB, Inflasi, Tingkat Pengangguran dan Kemiskinan, dan Abnormal Returns di Pasar Saham Indonesia - Utamaningsih, Arni (Jurusan Akuntansi Politeknik Negeri Padang, 2013)
This article describes the effect of fuel price increases on March 1, 2005 to GDP, inflation, unemployment and poverty, and the abnormal returns on the stock market. This study provides evidence that the rise in fuel prices on March 1, 2005 influences to the reduction in the growth of GDP, increasing inflation, increasing unemployment and poverty, as well as provide positive abnormal returns in 30 days of event windows, after the announcement of fuel price increases.